Renal Disease in Nepal, Under Microscope: One Year Study - Mainali, Nirajan; Acharya, Barsha; Lamichhane, Upasana; Phulara, Ganesh (Nepalese Medical Journal, 2024)
Introduction: Renal disease is a significant health problem in Nepal that is creating an increasing health and economic burden. Renal disease usually does not cause symptoms until reaching an advanced stage. Correct diagnosis of renal biopsy requires correlation of clinical, biochemical, and serological parameters and histopathological examination by light microscopy, immunofluorescence, and sometimes electron microscopic examination. The present study was conducted to study the histopathological patterns of all renal biopsy specimens in Nepal with the help of information obtained from Light microscopy and Immunofluorescence examination. Materials and Methods: In this cross-sectional (Prospective study) undertaken at the Pathology Department at Pratham Pathology Laboratory, Lazimpat for 1year duration (January 1ST - December 31ST 2022), all renal biopsy specimens of patients with different glomerular diseases were enrolled. The final diagnosis was made by a pathologist correlating with the histopathological along with immunofluorescence and other clinical and laboratory findings. Results: A total of 195 patient renal biopsy specimens between ages (1-80 years) were enrolled. The majority of patients were in the age group of 21-30 years (23.60%). The study showed slight female predominance with a male-to-female ratio of 1: 1.34. The most common renal disease was Lupus Nephritis with a frequency of 64 with a predominance of Lupus Type IV with a frequency of 34 (17.45. Among all, 21 cases were of Chronic Glomerulonephritis and the most common leading cause for it was IgA Nephropathy with a frequency of 8 (38.10%). Conclusions: The most commonly diagnosed renal disease under a microscope was Lupus Nephritis with a frequency of 34 (17.45%). The leading primary glomerular disease for Chronic glomerulonephritis was IgA Nephropathy with a frequency of 8 (38.10%).